Recent Progress in Transition Metal Complexes Catalyzed Hydrosilylation of Carbon-Carbon Multiple Bonds - Peng, Jiajian; Bai, Ying; Li, Jiayun; La, Guoqiao (Current Organic Chemistry, 2011)
Recent progress in the catalytic hydrosilylation of organic compounds containing carbon-carbon multiple bonds is reviewed. Hydrosilylation of carbon-carbon multiple bonds catalyzed with transition metal complexes remains the most commercially utilized process for formation of organosilicon compounds. During the last two decades, a number of simple and versatile catalytic systems including homogenous and heterogenous systems and even those for asymmetric catalysis procedures have been developed. These transition metal catalysts increased catalytic efficiency as well as regioselectivity and stereoselectivity.
Keywords: Hydrosilylation